Peran Grattitude Sebagai Strategi Coping untuk Menghadapi Fase Quarterlife Crisis Mahasiswa Universitas X di Palembang - Khairunisa; Ike Utia Ningsih (Jurnal Psikologi, 2025)
the quarterlife crisis is a challenging phase in early adulthood characterized by uncertainty, anxiety, and social pressure related to the future. This study explores gratitude as a coping strategy through a qualitative case study of subject IH. The analysis focuses on the subject’s experience applying four aspects of gratitude: intensity, frequency, span, and density. The findings reveal that gratitude effectively reduces stress and enhances mental resilience during this period. The subject’s consistent practice of gratitude helps shift focus away from negative thoughts and strengthens self-acceptance. Additionally, social support from family and friends further reinforces the coping mechanisms employed. These results highlight gratitude as an active practice that improves psychological well-being and assists individuals in managing the pressures of the quarterlife crisis. This study provides valuable insights into coping mechanisms within the Indonesian cultural context. It also suggests the need for gratitude-based interventions to support young adults’ mental health. Future research should involve a larger number of participants and examine how gratitude interacts with social support to develop more comprehensive coping strategies. Overall, this study paves the way for more effective psychological approaches to help individuals navigate the challenges of the quarterlife crisis